Gaze behavior reveals automaticity and attention allocation during music teaching vs. observing - Robin Heinsen (Bern Open Publishing, 2024)
In a unique case-study approach in which I served as both the research participant and the experimenter, I wore eye-tracking glasses while teaching a brief music lesson to two university students learning trumpet, then approximately two weeks later, I watched a video of the lesson and tracked my gaze again. To investigate unconscious perceptual processes engaged during music teaching, I compared my attention allocation while teaching to my attention allocation during self-observation. My gaze behavior while teaching revealed a high level of automaticity regarding lesson sequencing and allocation of attention. Strategic moment-to-moment shifts in attention between the two students occurred entirely below my conscious awareness, yet post hoc analyses revealed precisely timed changes that were related to momentary goals. While watching the video, absent the demands of behavioral interaction and momentary decision-making, I directed more sustained attention to both students than I had while teaching. These results reveal important features of "teacher thinking" that are not directly observable or typically construed as conscious behavior. That this component of teaching practice does not involve volitional control suggests that teachers' descriptions of their thinking may not reveal to novices important elements of pedagogical expertise.